In silico Characterization of Human Prion-Like Proteins: Beyond Neurological Diseases - Iglesias, Valentin; Paladin, Lisanna; Juan-Blanco, Teresa; Pallarès, Irantzu; Aloy, Patrick; Tosatto, Silvio C. E.; Ventura, Salvador (Frontiers in Physiology, 2019)
Prion-like behavior has been in the spotlight since it was first associated with the onset of mammalian neurodegenerative diseases. However, a growing body of evidence suggests that this mechanism could be behind the regulation of processes such as transcription and translation in multiple species. Here, we perform a stringent computational survey to identify prion-like proteins in the human proteome. We detected 242 candidate polypeptides and computationally assessed their function, protein-protein interaction networks, tissular expression and their link to disease. Human prion-like proteins constitute a subset of modular polypeptides broadly expressed across different cell types and tissues, significantly associated with disease, embedded in highly connected interaction networks and involved in the flow of genetic information in the cell. Our analysis suggests that these proteins might play a relevant role not only in neurological disorders, but also in different types of cancer and viral infections.